2019
DOI: 10.1080/17435390.2019.1687775
|View full text |Cite
|
Sign up to set email alerts
|

Length-dependent toxicity of TiO2 nanofibers: mitigation via shortening

Abstract: A mitigation strategy for the toxicity of TiO 2 nanofibers: high aspect ratio reduction Length and aspect ratio represent important toxicity determinants of fibrous nanomaterials. We have previously shown that anatase TiO 2 nanofibers (TiO 2 NF) cause a dose-dependent decrease of cell viability as well as the loss of epithelial barrier integrity in polarized airway cell monolayers. Herein we have investigated the impact of fiber shortening, obtained by ball-milling, on the biological effects of TiO 2 NF. Long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…They appear to be present in the workplace air as bundles, and some of the fibers detected by SEM during Study B were at least 5 µm and could therefore constitute a risk if inhaled. Bianchi et al [58] have recently shown that long (around 10 µm) TiO 2 NFs induce cell cytotoxicity in vitro and inflammation in vivo, while shortened (around 2 µm) TiO 2 NFs seem to mitigate the toxic effects, even without macrophages present in the in vitro cultures. SEM-analysis can also be used to quantify the particle concentration in the air.…”
Section: Measurements Of Airborne Titanium Dioxide Nanofibers and Nanmentioning
confidence: 99%
“…They appear to be present in the workplace air as bundles, and some of the fibers detected by SEM during Study B were at least 5 µm and could therefore constitute a risk if inhaled. Bianchi et al [58] have recently shown that long (around 10 µm) TiO 2 NFs induce cell cytotoxicity in vitro and inflammation in vivo, while shortened (around 2 µm) TiO 2 NFs seem to mitigate the toxic effects, even without macrophages present in the in vitro cultures. SEM-analysis can also be used to quantify the particle concentration in the air.…”
Section: Measurements Of Airborne Titanium Dioxide Nanofibers and Nanmentioning
confidence: 99%
“…TiO 2 exposure can cause a marked and widespread perturbation of the distribution of claudin-7 (red in the online version) and ZO-1 (green in the online version). Reproduced with permission [191]. Copyright 2020, Taylor & Francis Group.…”
mentioning
confidence: 99%
“…When applied to HUVECs, the cells apparently internalized more nanobelts compared with P25 at the same mass concentrations (Figure 4), indicating that the morphologies of TiO 2 materials altered their interactions with HUVECs. Previous studies also demonstrated that the different physicochemical properties of metal oxide based NMs altered their interactions with cells (Bianchi et al, 2020; Déciga‐Alcaraz et al, 2020; Jain et al, 2017; Medina‐Reyes et al, 2020; Simon et al, 2017). However, despite much higher internalization, P25 or nanobelts did not obviously lower cellular viability as measured by CCK‐8 and neutral red uptake assays (Figure 3), consistent with the point that Ti is a relatively biocompatible element (Luo et al, 2020; Wang, Zhong, Li, et al, 2021).…”
Section: Discussionmentioning
confidence: 93%